Kant on God - Byrne, Peter, 1950- (Ashgate studies in the history of philosophical theology., 2007)
Peter Byrne presents a detailed study of the role of the concept of God in Kant's Critical Philosophy. After a preliminary survey of the major interpretative disputes over the understanding of Kant on God, Byrne explores his critique of philosophical proofs of God's existence. Examining Kant's account of religious language, Byrne highlights both the realist and anti-realist elements contained within it. The precise role God plays in ethics according to Kant is then examined, along with the definition of religion as the recognition of duties as divine commands.